Relative Study on the Incompressible Fluid Flow Past a Porous Plate with and Without the Radiation Effect - Kuzhali, R.; Dharani, R. (International Journal of Engineering and Technology, 2018)
This paper focuses to compare the main flow velocity and temperature distribution in a three dimensional magneto hydrodynamic flow of a viscous incompressible fluid, past a vertical porous plate subjected to a periodic suction with and without the radiation effect. Governing equations are solved using perturbation technique and the results are discussed, on the results of the approximate solutions for velocity and temperature fields.Â